PERSEPSI GURU TERHADAP KEMAMPUAN BERPIKIR KRITIS DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Frilia Shantika Regina; S. Syihabuddin; Vismaia S. Damaianti (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2022)
The purpose of this study was to determine the perception of elementary school teachers regarding students' critical thinking skills in learning Indonesian. The research method used is descriptive qualitative method. Sources of data in this study were elementary school teachers. Data collection techniques by distributing questionnaires consisting of closed questions and open questions. Data analysis techniques in the form of data collection, data reduction, data display, and inference. The results of the study based on the results of data collection obtained as many as 56.92% of respondents strongly agree, 41.53% of respondents agree, and 1.53% of respondents disagree regarding the importance of critical thinking in SE students. Six aspects of critical thinking, namely interpretation, analysis, evaluation, inference, exposition, and self-regulation, the results obtained are 43.84% of respondents strongly agree, 55.38% of respondents agree, and 0.78% of respondents disagree. This figure shows that the teacher's response strongly agrees and agrees with the six aspects contained in critical thinking. In addition, the teacher also applies the six aspects of critical thinking in learning Indonesian in elementary schools, so that the process of critical thinking has begun to be given to elementary school students.